The Teacher’s Strategies in Overcoming Students’ Speaking Problems at SMAN 1 Selayar - Ria Rezeki; Sujarwo; Muliaty Ibrahim (CV. Eureka Murakabi Abadi, 2022)
The aim of this study was to find out the teacher’s strategy and students’ speaking problems at SMAN 1 Selayar. This study used mix method namely quantitative and qualitative. There were 215 students in the population. Then, there were 20 students and 1 teacher of of SMAN 1 Selayar as sample of study. Taking of sample was carried out by cluster random sampling. The instruments used observation, questionnaires and interview quides. The results of this study showed that some strategies used by teacher in overcoming students’ speaking problems at SMA Negeri 1 Selayar namely Role Play, Number Head Together, Discussion and Grouping. While, there were 13 (65%) students who said nothing in English as one of students’ speaking problem. Then, students thought to speak English as 9 (45%) students. The worry statement in making mistake to speak English was 8 (40%) students. Students felt nervous in speaking English as 11(55%) students. Students who were not confident were 7 (35%) students. It can be concluded that there are two dominant students’ speaking problem, namely students think nothing in speaking English and be nervous in speaking English. While, the dominant strategy is Role Play. The further researcher is recommended to be more detail finding problem faced by students in order for the teacher to apply strategy based on students’ need.